Ischemic Stroke, Glucocorticoids, and Remote Hippocampal Damage: A Translational Outlook and Implications for Modeling - Gulyaeva, Natalia V.; Onufriev, Mikhail V.; Moiseeva, Yulia V. (Frontiers in Neuroscience, 2021)
Progress in treating ischemic stroke (IS) and its delayed consequences has been frustratingly slow due to the insufficient knowledge on the mechanism. One important factor, the hypothalamic-pituitary-adrenocortical (HPA) axis is mostly neglected despite the fact that both clinical data and the results from rodent models of IS show that glucocorticoids, the hormones of this stress axis, are involved in IS-induced brain dysfunction. Though increased cortisol in IS is regarded as a biomarker of higher mortality and worse recovery prognosis, the detailed mechanisms of HPA axis dysfunction involvement in delayed post-stroke cognitive and emotional disorders remain obscure. In this review, we analyze IS-induced HPA axis alterations and supposed association of corticoid-dependent distant hippocampal damage to post-stroke brain disorders. A translationally important growing point in bridging the gap between IS pathogenesis and clinic is to investigate the involvement of the HPA axis disturbances and related hippocampal dysfunction at different stages of SI. Valid models that reproduce the state of the HPA axis in clinical cases of IS are needed, and this should be considered when planning preclinical research. In clinical studies of IS, it is useful to reinforce diagnostic and prognostic potential of cortisol and other HPA axis hormones. Finally, it is important to reveal IS patients with permanently disturbed HPA axis. Patients-at-risk with high cortisol prone to delayed remote hippocampal damage should be monitored since hippocampal dysfunction may be the basis for development of post-stroke cognitive and emotional disturbances, as well as epilepsy.